Discovering both sides of an unusual element: mercury - Cañari-Chumpitaz, Cristhian (2019)
The only liquid metal on the periodic table (at room temperature) that has changed the way we think on modern chemistry, introducing the concepts of pressure, vacuum and properties of gases, is mercury. Nevertheless, currently its high toxicity has made this element become a threat on public health. In this article we will describe the applications and hazards associated to this unique element.